Biological transformation of anthracene in soil by Pleurotus ostreatus under solid-state fermentation conditions using wheat bran and compost - Vargas, M. C.; Rodríguez, R.; Sánchez, F.; Ramírez, N. (CT&F - Ciencia, Tecnología y Futuro, 2001)
Postreatus was grown in a soil mixture contaminated with anthracene, wheat bran I and compost, in varying combinations. Assays with added bacteria and reinocularon of the fungus were also included. The results indicated that in many of the combinations, most of the anthracene was removed at the earliest sample time, 15 days. The most effective combination was spiked (anthracene-added) soil, fungus and compost and the addition of acclimated bacteria to this mixture inhibited anthracene removal. Analyses of extracts by high-pressure liquid chromatography (HPLC) indicated that -anthraquinone, was the major metabolite formed. The results of this study indicate that solid-state fermentation of anthracene-contaminated soils using P. ostreatus in combination with wheat bran and compost additives can produce an accelerated rate of biological removal of anthracene from the soil.